If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6E + -16 = 10E + 38 Reorder the terms: -16 + 6E = 10E + 38 Reorder the terms: -16 + 6E = 38 + 10E Solving -16 + 6E = 38 + 10E Solving for variable 'E'. Move all terms containing E to the left, all other terms to the right. Add '-10E' to each side of the equation. -16 + 6E + -10E = 38 + 10E + -10E Combine like terms: 6E + -10E = -4E -16 + -4E = 38 + 10E + -10E Combine like terms: 10E + -10E = 0 -16 + -4E = 38 + 0 -16 + -4E = 38 Add '16' to each side of the equation. -16 + 16 + -4E = 38 + 16 Combine like terms: -16 + 16 = 0 0 + -4E = 38 + 16 -4E = 38 + 16 Combine like terms: 38 + 16 = 54 -4E = 54 Divide each side by '-4'. E = -13.5 Simplifying E = -13.5
| (2x+3)=(x+5) | | -7(-3)+2(-9)=3 | | -2T+25=0 | | 90-4x=0.6x^2-12x+80 | | 0.4x-0.2(4-x)=2.5 | | 0.693x=x+1 | | -4(8n-1)=19+32n | | 1.386x=1+2 | | 6x-49=17 | | -7(8)+2(4)=3 | | 6x-4(2-x)=8 | | 4a-3b+5c=16 | | 27-17=2(x-1) | | 20x=ex+3 | | 30x-4+6x-10x-13= | | 2/x-6=7x | | 30-4+6x-10-13= | | -5+10y+10=14+13y-24 | | 15x+4=x+4 | | 6(45x-18)+34=7(7x+16)-10 | | N+-9=-24 | | -t^2+9t-8=0 | | 5=8b+13 | | 5y-9=-41 | | 8/12=(x-4)/20 | | 5x-2=2x+20 | | 6(45x-18)=7(7x+16)-10 | | 14-6x=-8x+18 | | y=2y-17 | | 3(3y+7)-24= | | 9x+4-5x=8x-6+x | | 7y+4=6y-8 |